2014
DOI: 10.1111/ecin.12069
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Restaurant Calorie Labels on Food Choice: Results From a Field Experiment

Abstract: Using field experiment data, we compare the effectiveness of calorie labels to a “fat tax” at reducing calories ordered. Results from a structural model of consumer demand show that numeric labels did not influence food choice, but symbolic traffic light labels caused restaurant patrons to select lower‐calorie menu items; thus, adding a traffic light symbol could enhance the effectiveness of the numeric calorie label (as currently proposed by the Food and Drug Administration). Additionally, our model projects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 46 publications
0
64
2
Order By: Relevance
“…Of the 28 studies included in the review, 17 were RCTs: 16 of these were randomised by individual (Cavanagh 2014; Crockett 2014; Ebneter 2013; Ellison 2013; Ellison 2014a; Girz 2012 - study 1; Girz 2012 - study 2; Girz ongoing; Hammond 2013; Harnack 2008a; James 2015; Platkin 2014; Roberto 2010; Roberto 2012; Temple 2010; VanEpps 2016), while one was randomised by cluster, with vending machines being the unit of randomisation (Bergen 2006). In addition, there were five Q-RCTs (Allan 2015; Kral 2002; Vermeer 2011; Wansink 2006 - study 1; Wansink 2006 - study 3), plus six ITS studies (Balasubramanian 2002; Bollinger 2011; Chu 2009; Cioffi 2015; Dubbert 1984; Holmes 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 28 studies included in the review, 17 were RCTs: 16 of these were randomised by individual (Cavanagh 2014; Crockett 2014; Ebneter 2013; Ellison 2013; Ellison 2014a; Girz 2012 - study 1; Girz 2012 - study 2; Girz ongoing; Hammond 2013; Harnack 2008a; James 2015; Platkin 2014; Roberto 2010; Roberto 2012; Temple 2010; VanEpps 2016), while one was randomised by cluster, with vending machines being the unit of randomisation (Bergen 2006). In addition, there were five Q-RCTs (Allan 2015; Kral 2002; Vermeer 2011; Wansink 2006 - study 1; Wansink 2006 - study 3), plus six ITS studies (Balasubramanian 2002; Bollinger 2011; Chu 2009; Cioffi 2015; Dubbert 1984; Holmes 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Second, due to sampling convenience, the focus has largely been on food service provision within the public sector (i.e. school, university and work canteens) which imposes limitations due to a specific nature of the audiences this type of business ventures caters for (Ellison et al 2014;Price et al 2016). Third, not all food qualities have been thoroughly looked into; the carbon intensity of menu items, for instance, has been investigated only sporadically (Pulkkinen et al 2016).…”
Section: 2the Role Of Menu Designmentioning
confidence: 99%
“…Since the implementation of mandatory CL in the USA (11) numerous observational and experimental studies have been conducted in various settings to assess its impact on food choice and EI, many of which have shown positive effects (39,(52)(53)(54) . However, a recent extensive review of the related literature reported no clear patterns due to a lack of comparability across studies.…”
Section: Menu Labellingmentioning
confidence: 99%